Analysis of Raw Material Inventory Control using the ABC Analysis Method and EOQ Method in the Fajar Onion Crackers Business - Ledy Vanesa; Helma, Helma (Universitas Negeri Padang, 2023)
Inventory control is one aspect that affect the company's smooth operation. In this study, the Activity Based Costing (ABC) analysis method and the Economic Order Quantity (EOQ) method are applied to control raw material inventory. The Bawang Fajar cracker business is one of the SMEs whose raw material inventory control has yet to use the ABC analysis method and the EOQ method. This research is applied research. Based on the results of this study, it was found that the grouping of raw material inventories according to ABC analysis was divided into three groups, namely group A; wheat flour and cooking oil, group B; eggs, and group C; onion and garlic. The TIC value based on the EOQ method is Rp. 1,749,102.00, while the TIC value based on the method used by the company is Rp. 3,582,200.00. So that the EOQ method is more effective than the method used by the company in the Fajar Bawang Crackers Business.